ROMS Based Hydrodynamic Modelling Focusing on the Belgian Part of the Southern North Sea - Georgios Klonaris; Frans Van Eeden; Jeffrey Verbeurgt; Peter Troch; Denis Constales; Hans Poppe; Alain De Wulf (Journal of Marine Science and Engineering, 2021)
The North Sea is a shallow sea that forms a complex physical system. The nonlinear interaction of the astronomical tides, varying wind fields and varying pressure systems requires appropriate approaches to be described accurately. An application based on the advanced numerical model Regional Ocean Modeling System (ROMS) was newly developed by the authors, tailored to simulate these hydrodynamic processes in the North Sea and the Belgian Continental Shelf, which is the area of particular interest in the present study. The purpose of this work is to develop and validate a state-of-the-art three-dimensional numerical model to form the basis of a compound operational and forecasting tool for the Belgian coastal zone. The model was validated with respect to water levels and temperature. Validation for astronomical tides was accomplished through the comparison of the principal constituents between the model results and observations at a number of tidal gauges in Belgium and other countries. A statistical analysis of the results showed that the model behaves as expected throughout the North Sea. The model response to the varying meteorological conditions was also validated using hindcast data for 2011 as input. In this case, the comparison between observed and modelled water levels showed a good agreement with average RMSE in Belgium 9.5 cm. Overall, the added value of this work is the development of an independent model for validation and comparison with other models and which can be used as an efficient tool for operational and forecasting purposes.